Development and Validation of a Prognostic Index Based on Genes Participating in Autophagy in Patients With Lung Adenocarcinoma - Wu, Zi-Xuan; Huang, Xuyan; Cai, Min-Jie; Huang, Pei-Dong; Guan, Zunhui (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma (LUAD) is a deadly respiratory system malignancy with poor prognosis. Autophagy is essential for the beginning, development, and therapy resistance of cancer. However, the expression of genes participating in autophagy in LUAD and their associations with prognosis remain unclear. Methods: Predictive genes participating in autophagy in LUAD samples from The TCGA and GEO datasets were investigated. The TCGA and GEO cohorts were divided into two risk groups, while the low-risk group having a longer overall survival time (OS).This article aims to point out the interaction between genes participating in autophagy and immune function, immune checkpoints, and m6a in LUAD. The prediction model was designed for exploring Lasso regression. It has been revealed that gene expression and autophagy are inextricably connected. Results: genes participating in autophagy were shown to be somewhat overexpressed in high-risk even no different clinical symptoms were present, indicating that they mighg be used in a model to predict LUAD prognosis. The majority of genes participating in autophagy prognostic signatures controlled immunological and tumor-related pathways, according to GSEA. KRT6A, KYNU, IGFBP1, DKK1, PKP2, PLEK2, GAPDH, FLNC, and NTSR1 might be related to the oncology process for LUAD patients. CERS4, CMAHP and PLEKHB1 have been identified as being associated with low risk in patients with LUAD. Furthermore, the immune function and m6a gene expression differed significantly between the two groups. Conclusions: genes participating in autophagy are connected to the development and progression of LUAD. LUAD patients' prognoses are often foreseen utilizing matched prognostic models. genes participating in autophagy in LUAD may be therapeutic targets that ought to be investigated more.